2006
DOI: 10.1002/prot.20961
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of axolotl (Ambystoma mexicanum) liver bile acid‐binding protein bound to cholic and oleic acid

Abstract: The family of the liver bile acid-binding proteins (L-BABPs), formerly called liver basic fatty acid-binding proteins (Lb-FABPs) shares fold and sequence similarity with the paralogous liver fatty acid-binding proteins (L-FABPs) but has a different stoichiometry and specificity of ligand binding. This article describes the first X-ray structure of a member of the L-BABP family, axolotl (Ambystoma mexicanum) L-BABP, bound to two different ligands: cholic and oleic acid. The protein binds one molecule of oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
(67 reference statements)
1
15
0
1
Order By: Relevance
“…somewhat smaller than the equivalent value for chicken L-BABP, 627.4 Å 3 (11), and axolotl L-BABP, 685.5 Å 3 (15)). All of these values are significantly larger that the value observed for the apo form of chicken L-BABP, 143.7 Å 3 (11).…”
Section: Structure and Ligand-binding Stoichiometry Of The Wild Typementioning
confidence: 70%
See 3 more Smart Citations
“…somewhat smaller than the equivalent value for chicken L-BABP, 627.4 Å 3 (11), and axolotl L-BABP, 685.5 Å 3 (15)). All of these values are significantly larger that the value observed for the apo form of chicken L-BABP, 143.7 Å 3 (11).…”
Section: Structure and Ligand-binding Stoichiometry Of The Wild Typementioning
confidence: 70%
“…2 prompted us to design the G55R mutant of zebrafish L-BABP. The sequences of five L-BABPs are aligned in the figure, and the amino acids involved in ligand binding in the only two structures of co-crystals that were known, chicken (11) and axolotl (15), are indicated with white and black dots. Six amino acids participate in the binding in both species, and five (Tyr 14 , Thr 53 , Phe 96 , His 98 , and Gln 100 ) are conserved in all of the sequences.…”
Section: Structure and Ligand-binding Stoichiometry Of The Wild Typementioning
confidence: 99%
See 2 more Smart Citations
“…So far, L-BABP has never been found in mammalian species, but it has been identified and characterized in some vertebrates including fish, amphibians, reptiles, and birds (Ceciliani et al, 1994;Di Pietro et al, 1996Córdoba et al, 1999;Denovan-Wright et al, 2000;Ko et al, 2004;Jordal et al, 2006). Recent research on the structure of the L-BABP crystal showed that the capacity of L-BABP for binding to long-chain fatty acids is weak, but is strong for bile acid (Schievano et al, 1994;Beringhelli et al, 2001;Guariento et al, 2008), which is consistent with the presumption that the main function of L-BABP is to transport bile acids rather than fatty acids in chicken (Nichesola et al, 2004;Capaldi et al, 2006).…”
Section: Introductionmentioning
confidence: 55%